Captive Offshoring, Innovation and Market Diffusion: Evidence from the Swedish Community Innovation Survey - Torben Schubert (Journal of the Knowledge Economy, 2023)
Although the effects of captive offshoring on firm innovation have increasingly become a subject of study, the literature did so far not distinguish between the effects on introducing innovation as opposed to the effects their market diffusion. This distinction is important. By integrating insights from the innovation diffusion literature, we argue that the effects of captive offshoring on home base innovation are likely to differ between the generation and the diffusion phases. Using a matched employer-employee panel dataset drawn from consecutive waves of the Swedish Community Innovation Survey (CIS) between 2009 and 2015, it is shown that captive offshoring, as measured by the share of employees at foreign locations, has an inverted u-shape effect on innovation propensity (with positive effects for the average firm). In contrast, employment offshoring does not, on average, affect the rate of diffusion as measured by the share of turnover from new products. For firms with more novel product innovations, the effects are even negative.
Keywords: M14; M16; O32; 330; International employment; Innovation; Diffusion; Community innovation survey; Sweden